Pulse and Vital Sign Measurement in Mixed Reality using a HoloLens - McDuff, Daniel; Hurter, Chrisophe; Gonzalez Franco, Mar (23rd ACM Symposium on Virtual Reality Software and Technology (VRST), 2017)
Cardiography, quantitative measurement of the functioning of the heart, traditionally requires customized obtrusive contact sensors. Using new methods photoplethysmography and ballistocardiography signals can be captured using ubiquitous sensors, such as webcams and accelerometers. However, these signals are not visible to the unaided eye. We present Cardiolens - a mixed reality system that enables real-time, hands-free measurement and visualization of blood flow and vital signs from multiple people. The system combines a front-facing webcam, imaging ballistocardiography, and remote imaging photoplethysmography methods for recovering pulse signals. A heads up display allows users to view their own heart rate whenever they are wearing the device and the heart rate and heart rate variability of another person simply by looking at them. Cardiolens provides the wearer with a new way to understand physiological signals and has applications in human-computer interaction and in the study of social psychology.